Complement peptide receptors (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Cianciulli, Antonia; Coulthard, Liam; Hawksworth, Owen; Lee, John D.; Li, Xiang X.; Mitolo, Vincenzo; Monk, Peter; Panaro, Maria A.; Woodruff, Trent M.
No abstract available